1967
DOI: 10.1113/jphysiol.1967.sp008317
|View full text |Cite
|
Sign up to set email alerts
|

Effects of haemorrhage on the distribution of the peripheral blood flow in the rabbit

Abstract: SUMMARY1. The effects of bleeding unanaesthetized rabbits by 26% of their blood volume on the blood flow in the portal, renal, muscle and skin beds were investigated in normal animals, in animals without functioning autonomic effectors, and in animals with section of the carotid sinus and aortic nerves.2. In animals without functioning autonomic effectors there was progressive vasodilatation during the 4 hr following haemorrhage, which differed markedly in the different regional beds studied. The dilatation wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1972
1972
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…There is good evidence that, in anesthetized animals, the output of cardiopulmonary receptor reflexes is not directed uniformly among the various vascular beds, but influences predominantly the kidney (Brown, 1979;Thoren, 1979). Moreoever, Chalmers et al (1967c) found, when studying the effects of hemorrhage on regional vascular resistance in conscious rabbits, that only in the case of the kidney did vasoconstriction occur that could not be accounted for by the arterial baroreceptor reflex. It is quite likely, therefore, that in our present study a major effect of the cardiac receptor reflex on the renal vasculature during blood volume depletion was concealed by the absence of 433 effects on other vascular beds.…”
Section: Discussionmentioning
confidence: 96%
“…There is good evidence that, in anesthetized animals, the output of cardiopulmonary receptor reflexes is not directed uniformly among the various vascular beds, but influences predominantly the kidney (Brown, 1979;Thoren, 1979). Moreoever, Chalmers et al (1967c) found, when studying the effects of hemorrhage on regional vascular resistance in conscious rabbits, that only in the case of the kidney did vasoconstriction occur that could not be accounted for by the arterial baroreceptor reflex. It is quite likely, therefore, that in our present study a major effect of the cardiac receptor reflex on the renal vasculature during blood volume depletion was concealed by the absence of 433 effects on other vascular beds.…”
Section: Discussionmentioning
confidence: 96%
“…Chalmers et al (11) observed that after sinoaortic denervation in the rabbit a 26% hemorrhage produced a small but sustained increase in renal vascular resistance. Oberg and White (1) demonstrated that after sinoaortic denervation in the cat a 20-ml hemorrhage caused an increase in the vascular resistance in the kidney greater than that in the muscular bed.…”
Section: Discussionmentioning
confidence: 99%
“…The efferent pathway also appears to be the same: an increase in sympathetic tone is followed by withdrawal of the sympathetic system, as shown by the sudden decrease in BP and also by micro-neurographic recordings [12,49,60,67], and then by an increase in vagal tone, as shown by the slowing of HR. Since the vasovagal reflex during hemorrhagic shock has been observed in rats, rabbits, cats, dogs and monkeys, as well as in humans [12,14,22,38,49,50,52,57,59,67], this means that the orthostatic vasovagal reflex is predisposed in primates and other mammals.…”
Section: Discussion J the Clotting And The Conflict Theoriesmentioning
confidence: 99%
“…The vasovagal reflex during hemorrhagic shock has been observed in mammals such as rats, rabbits, cats, dogs and rhesus monkeys, as well as in humans [12,14,23,38,49,50,52,57,59,67]. The hemodynamic response to acute central hypovolemia consists of two phases.…”
Section: J Fear and Threat Bradycardia In Animalsmentioning
confidence: 99%